2019
DOI: 10.1111/cas.13987
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of DLEU2 suppresses pancreatic cancer cell proliferation and invasion by upregulating microRNA‐455

Abstract: Long noncoding RNA (lnc RNA ) DLEU 2 has been shown to be dysregulated in several type of tumor. However, the potential biological roles and molecular mechanisms of DLEU 2 in pancreatic cancer ( PC ) progression are poorly understood. In this study, we found that the DLEU 2 level was substantially upregulated in PC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…LncR-NAs have emerged as novel potential therapeutic target tools, and studies have demonstrated that lncRNAs are significantly associated with the progression of PC [47]. For example, high DLEU2 levels indicate a poor prognosis for PC patients [12]. SNHG1 inhibits PC cell proliferation, invasion and metastasis by inhibiting the Notch-1 signaling pathway [48].…”
Section: Lncrnas Related To Pcmentioning
confidence: 99%
See 3 more Smart Citations
“…LncR-NAs have emerged as novel potential therapeutic target tools, and studies have demonstrated that lncRNAs are significantly associated with the progression of PC [47]. For example, high DLEU2 levels indicate a poor prognosis for PC patients [12]. SNHG1 inhibits PC cell proliferation, invasion and metastasis by inhibiting the Notch-1 signaling pathway [48].…”
Section: Lncrnas Related To Pcmentioning
confidence: 99%
“…However, DLEU2 is not an independent biomarker for PC prognosis. Thus, the regulation of DLEU2/miR-455/ SMAD2 can be considered a PC therapeutic axis [12].…”
Section: Dleu2mentioning
confidence: 99%
See 2 more Smart Citations
“…, acute myeloid leukemia(31), glioma(36), hepatocellular carcinoma(37,38), esophageal cancer(39,40), osteosarcoma(41), and pancreatic cancer(42) tissues and cell lines, and its expression level is related to the patient's prognosis and overall survival closely related. Furthermore, knockdown of lncRNA DLEU2 inhibited the proliferation of AGS and MKN-45 cells, and induced cell apoptosis.…”
mentioning
confidence: 99%